Subtle direction or collegial support? A mathematics teacher’s visual attention to teaching partners - Haataja, Eeva; Salonen, Reito Visajaani (LUMAT: International Journal on Math, Science and Technology Education, 2025)
Co-teaching can benefit learning and well-being of all students in inclusive classrooms. In Finland, co-teaching is a pivotal method of support for students with special needs in learning mathematics, but the outcomes are dependent on the quality of co-teaching. However, little is known about how effective co-teaching is situationally constructed in classrooms. The aim of this study was to pilot the approach to investigate the patterns of teaching partners’ interaction in mathematics education. This mixed-method case study charts visual attention between teaching partners in mathematics education. The data was collected with mobile eye tracking in four mathematics lessons with the same mathematics teacher and his seventh-grade students. This study provides introductory information on how a mathematics teacher attends to the co-teaching partners during instruction with short glances during mathematics teacher’s instruction, and long dwells when listening to the teaching partner. Our findings indicate that teacher’s attention to the teaching partners was relative to the pedagogical and interactional situations and often took place during moments with emotional triggers to the teacher.